The interaction of AB-680, a CD73 inhibitor, with NBTI, a nucleoside transporter inhibitor, on the adenosinergic control of atrial contractility - Ovari, Ignac; Brezniczky, Agnes Boglarka; Laczovics, Attila; Berényi, Ervin; Erdei, Tamas; Ojo, Oluwatofunmi; Hornok, Bence; Juhasz, Bela; Szilvassy, Zoltan; Zsuga, Judit; Viczjan, Gabor; Gesztelyi, Rudolf (Frontiers in Pharmacology, 2025)
IntroductionIn this study, we investigated the influence of AB-680, a highly potent CD73 inhibitor, on the effect of NBTI, a nucleoside transport blocker, exerted on concentration-effect (E/c) curves generated with CPA, a relatively stable, selective A1 adenosine receptor full agonist, in isolated, paced guinea pig left atria.MethodsTransformations of the CPA E/c curves, constructed in the absence and presence of AB-680 and NBTI (in all combinations), were used to assess the changes in the interstitial adenosine concentration. These changes were quantified with the receptorial responsiveness method (RRM), a unique procedure providing the CPA concentration (as cx), which is equieffective with the increase in the interstitial adenosine concentration caused by NBTI. AB-680 and NBTI were dissolved in DMSO (recommended for in vitro use) as well as in a buffer (recommended for in vivo use), and the results were compared.Results and discussionWe found that AB-680, when added alone, did not affect the response to CPA. In turn, AB-680, when administered together with NBTI, was able to partially reverse the elevating effect of NBTI on the interstitial adenosine level. Nevertheless, the inhibitory action of AB-680 on the effect of NBTI appeared to be smaller than that of PSB-12379, another CD73 inhibitor investigated earlier in the same experimental model. We also found that DMSO interfered with our measurements to a lesser extent than the buffer recommended for in vivo studies. In addition, AB-680, when co-administered with NBTI (both dissolved in DMSO), reduced cx (i.e. probably also the surplus interstitial adenosine) by at least half.